Effect of Turbulence Intensity on Megawatt Wind Turbines - OUYANG Hua; WU Faming; WANG Dian; WANG Lei; LI Huixing (Kongzhi Yu Xinxi Jishu)
Effect of turbulence intensity on wind turbines is analyzed in this paper. Simulation has been conducted for limit load, fatigue load and performance of wind turbines at three different turbulence intensity I15= 0.18,0.16,0.14 by taking 1 650 kW variable speed wind turbine as an example. Simulation results show that with the turbulence intensity increasing, both fatigue and limit load of wind turbine will increase correspondingly and its performance will degrade to some extent.